Prevalence of Cam Morphology in Females with Femoroacetabular Impingement - Levy, David M.; Hellman, Michael D.; Harris, Joshua D.; Haughom, Bryan; Frank, Rachel M.; Nho, Shane J. (Frontiers in Surgery, 2015)
Cam and pincer are two common morphologies responsible for femoroacetabular impingement (FAI). Previous literature has reported that cam deformity is predominantly a male morphology, while being significantly less common in females. Cam morphology is commonly assessed with the alpha angle, measured on radiographs. The purpose of this study is to determine the prevalence of cam morphology utilizing the alpha angle in female subjects diagnosed with symptomatic FAI. All females presenting to the senior author’s clinic diagnosed with symptomatic FAI between December 2006 and January 2013 were retrospectively reviewed. Alpha (α) angles were measured on anteroposterior and lateral (Dunn 90°, cross-table lateral, and/or frog-leg lateral) plain radiographs by two blinded physicians, and the largest measured angle was used. Using Gosvig et al.’s classification, alpha angle was characterized as (pathologic > 57°), borderline (51–56°), subtle (46–50°), very subtle (43–45°), or normal (≤42°). Three hundred and ninety-one patients (438 hips) were analyzed (age 36.2 ± 12.3 years). Among the hips included, 35.6% were normal, 14.6% pathologic, 15.1% borderline, 14.6% subtle, and 20.1% very subtle. There was no correlation between alpha angle and patient age (R = 0.17) or body mass index (R = 0.05). The intraclass correlation coefficient for α-angle measurements was 0.84. Sixty-four percent of females in this cohort had an alpha angle >42°. Subtle cam deformity plays a significant role in the pathoanatomy of female patients with symptomatic FAI. As the majority of revision hip arthroscopies are performed due to incomplete cam correction, hip arthroscopists need to be cognizant of and potentially surgically address these subtle lesions.